Carrageenan as an alternative coating for papaya (Carica papaya L. cv. Eksotika). - Mustaffa Hamzah, Hanisah; Osman, Azizah; Tan, Chin Ping; Mohamad Ghazali, Farinazleen (Elsevier, 2013)
Edible coatings are gaining popularity compared to other types of packaging due to their more environmental friendly nature and ability to carry active ingredients. In this study, a two-factor central composite design (CCD) was used to optimize a carrageenan-based edible coating formulation for coating of ‘Eksotika’ papayas. The effect of a carrageenan-based [carrageenan (0.2–0.8%, w/v) and glycerol (0–1%, w/v)] coating on firmness and colour components (L, a and b values) of papaya was evaluated. From the optimization study, no significant (p > 0.05) lack of fit was found for the reduced model for all response variables (firmness, L, a and b values) tested. Coefficients of determination (R2) ranging from 0.767 to 0.952 were obtained for these responses. From the multiple response optimization analysis, a combination of 0.78% (w/v) carrageenan with 0.85% (w/v) glycerol for a carrageenan-based coating was predicted to give desirable effects for the response variables tested, with no significant (p > 0.05) differences between the experimental and predicted values.